Oxygen-regulated and transactivating domains in endothelial PAS protein 1: comparison with hypoxia-inducible factor-1alpha. - O'Rourke, J; Tian, Y; Ratcliffe, P; Pugh, C (1999)
Endothelial PAS protein 1 (EPAS1) is a basic helix-loop-helix Per-AHR-ARNT-Sim transcription factor related to hypoxia-inducible factor-1alpha (HIF-1alpha). To analyze EPAS1 domains responsible for transactivation and oxygen-regulated function, we constructed chimeric fusions of EPAS1 with a GAL4 DNA binding domain, plus or minus the VP16 activation domain. Two transactivation domains were defined in EPAS1; a C-terminal domain (amino acids 828-870), and a larger internal domain (amino acids 517-682). These activation domains were interspersed by functionally repressive sequences, several of which independently conveyed oxygen-regulated activity. Two types of activity were defined. Sequences lying N-terminal to and overlapping the internal transactivation domain conferred regulated repression on the VP16 transactivator. Sequences lying C-terminal to this internal domain conveyed repression and oxygen-regulated activity on the native EPAS1 C-terminal activation domain, but not the Gal/VP16 fusion. Fusions containing internal but not C-terminal regulatory domains manifested regulation of fusion protein level. Comparison of EPAS1 with HIF-1alpha demonstrated a similar organization for both proteins, and for the C terminus defined a conserved RLL motif critical for inducibility. Overall, EPAS1 sequences were less inducible than those of HIF-1alpha, and inducibility was strikingly reduced as their expression level was increased. Despite these quantitative differences, EPAS1 regulation appeared similar to HIF-1alpha, conforming to a model involving the modulation of both protein level and activity, through distinct internal and C-terminal domains.